Ambient temperature ZrO2-doped TiO2 crystalline photocatalysts: Highly efficient powders and films for water depollution. (September 2019) - Mahy, Julien G.; Lambert, Stéphanie D.; Tilkin, Rémi G.; Wolfs, Cédric; Poelman, Dirk; Devred, François; Gaigneaux, Eric M.; Douven, Sigrid
Abstract: In this paper, several TiO2 materials doped with zirconia precursor (0.7, 1.4, 1.6 and 2.0 mol%) were synthesized by an easy aqueous sol-gel synthesis at ambient temperature. This method consists in the peptization of the TiO2 colloid in presence of HNO3 . The corresponding pure TiO2 material was also synthesized for comparison. The performances and the physico-chemical properties of these materials were compared to the well-known Evonik P25 photocatalyst. The physico-chemical characterizations showed that nano-crystalline anatase-brookite particles were produced with the sol-gel process, with higher specific surface area than P25 (∼200 m 2 g -1 vs. 47 m 2 g -1 ). All samples presented a higher visible absorption than P25. The XPS spectra showed that all the samples were doped with nitrogen and that mixed TiO2 –ZrO2 oxide materials were obtained when doping with zirconia precursor. Photoactivity was evaluated through the degradation of p -nitrophenol in water. On the one hand, under UV/visible light, the ZrO2 doping increased the degradation efficiency of the pure TiO2 catalyst due to a better charge separation in the mixed TiO2 –ZrO2 oxides. The activity of the sample with the highest dopant content was even higher than the one of P25. On the other hand, under visible light, all samples were much more efficient than P25. This activity shift towards visible range was due to the N-doping of the catalysts, with a slight improvement for the doped ones. Finally, the feasibility of producing films starting from an aqueous suspension of the photocatalyst was assessed on P25, pure TiO2 and the best doped material. The photoactivity of these films, evaluated on the degradation of methylene blue under UV-A light, showed that the sample with the highest dopant concentration had an efficiency 4 times higher than pure TiO2 and 20 times higher than P25. Graphical abstract: Image 1 Highlights: TiO2 –ZrO2 colloids synthesized by aqueous sol-gel method. Anatase-brookite TiO2 nanoparticles with high specific surface area. N-doping observed with all samples. Highly active photocatalysts under UV and visible lights. Efficient degradation both for the powder and for the film photocatalysts.